2017
DOI: 10.1080/03075079.2017.1368475
|View full text |Cite
|
Sign up to set email alerts
|

Establishing world-class universities in China: deploying a quasi-experimental design to evaluate the net effects of Project 985

Abstract: The rapid advances of China's universities in major international league tables are generally believed to be an accomplishment of Project 985. A quasi-experimental study was, therefore, undertaken to test the belief and evaluate the effectiveness of this policy intervention, using 15-year panel data between 1998 and 2013. Results from a difference-indifferences model showed that Project 985 had a positive effect on publication outputs of '985' universities. Tier 2 '985' universities gained strong momentum in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 29 publications
0
61
0
Order By: Relevance
“…They show that, in general, there is an increase in the number of publications in international journals after universities joined this program, but the publication activity of participants is significantly different. A more recent studу criticizes Zhang et al's methodology but confirms the publication growth, albeit finding a "homogenizing trend within 985 universities" (Zong and Zhang 2017). For many government university excellence programs, publication output is a key indicator of successful participation..…”
Section: Excellence Initiatives In Different Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…They show that, in general, there is an increase in the number of publications in international journals after universities joined this program, but the publication activity of participants is significantly different. A more recent studу criticizes Zhang et al's methodology but confirms the publication growth, albeit finding a "homogenizing trend within 985 universities" (Zong and Zhang 2017). For many government university excellence programs, publication output is a key indicator of successful participation..…”
Section: Excellence Initiatives In Different Countriesmentioning
confidence: 99%
“…In addition, at this stage of the program, it is difficult to assess how the policy of global integration of Japanese universities will lead to qualitative improvements in the system. Zong and Zhang (2017) studying the Chinese project 985, also note that the publication gap between different types of universities is growing as a result of the excellence initiative.…”
Section: Excellence Initiatives In Different Countriesmentioning
confidence: 99%
“…The study of Chinese universities participating in Project-985 by Zhang et al (2013) found that the rate of growth of publications for universities as a whole increased more quickly after the implementation of the ExIn. A quasi-experimental study based on DID conducted by Zong and Zhang (2017) to evaluate the effectiveness of Project-985, using 15-year panel data (1998-2013) also showed that the Project-985 had a positive effect on publication output of participating universities.…”
Section: Potential Effects On Publication Activitymentioning
confidence: 98%
“…To establish causality between the increase in the amount of PBF and university performance in the subsequent periods, we employ the difference-in-differences (DID) estimator. This approach is widely used to evaluate the effect of the policy intervention by comparing the variation in an outcome variable over time between the treatment and the control group (Pedraja-Chaparro 2016; Zong and Zhang, 2019). Considering the obtainment of more resources from the government as a policy intervention (treatment), we calculate the effect of this increase on the set of performance indicators (outcome variables).…”
Section: Estimating the Causal Effect Of The Policymentioning
confidence: 99%